Hubungan Paritas, Penolong Persalinan dan Jarak Kehamilan dengan Angka Kematian Bayi di Jawa Timur - Renaldi Kurniawan; Soenarnatalina Melaniani (Jurnal Biometrika dan Kependudukan (Journal of Biometrics and Population), 2018)
Infant mortality is a major component in determining the health and well-being of a community in a country. Indonesia Health Demographic Survey in 2012 shows that infant mortality rate in Indonesia is 32 babies per 1000 live births. Infant mortality rate in eastern Java is 26 babies per 1000 live births. Infant mortality is caused by external factors and internal factors. Parity, gestational distance and birth attendant are the factors chosen to be analyzed. The objectives of the study were to analyze the relationship of parity, birth spacing and birth attendant to infant mortality rate in East Java. The type of research that is analytical research using non-reactive approach. The study took the data of the 2012 IDHS Female Woman Never married. Sampling followed the 2012 IDHS plus inclusion criteria from the researchers. The number of samples of the study was 591 mothers with a history of dead infants during the survey. The study took the data of the 2012 SDKI Female Woman Never married. Data analysis was done by multiple logistic regression. The results of the simple logistic regression analyzes have shown an association between parity> 2 children, birth attendants instead by a health professional, pregnancy spacing ≤ 4 years and spacing of pregnancy> 4 years. All independent variables entered as a candidate for the multiple logistic regression analysis of the results of the multiple logistic regression analysis was parity shows, their relationship with infant mortality with p value = 0.001, but at birth attendant with a p value of 0.66. Screening risks of pregnant mothers and handling of ill toddlers by midwives and IEC to mothers about nutrition, pregnancy care and infant care through counseling, leaflets and posters.